The Correlation between Age, Years of Service, and Working Postures and the Complaints of Musculoskeletal Disorders - Buntari Asmaning Putri (Universitas Airlangga, 2019)
ABSTRACTIntroduction: Musculoskeletal Disorders (MSDs) is one of the health problems caused by the used equipment or performed activity while working. The workers in the packaging section of the iron and steel industry who do the packaging process manually are exposed to the risk of experiencing MSDs due to the working attitudes and non-ergonomic postures. This study aims to identify the correlation between ages, years of service, as well as working postures and the complaints of MSDs experienced by the workers of the packaging section of iron and steel industry in Sidoarjo. Methods: This study applied a cross-sectional design. The research population was all workers in the packaging section of an iron and steel industry in Sidoarjo, reaching 27 people. The research samples are the total population of the workers in the packaging section of an iron and steel industry in Sidoarjo. The risk assessment of MSDs was carried out by using the Rapid Entire Body Assessment (REBA) method, while the risk complaints were measured by using the Nordic Body Map (NBM) questionnaire. The data were tested by using Chi-Square. Results: The results revealed that there were moderate correlations between the age and the MSDs complaints (phi coefficient=0.335), between the years of service and the MSDs complaints (phi coefficient=0.433), and between the working postures and MSDs complaints (phi coefficient=0.401). Conclusion: The moderate-level of correlation still affected the occurrence of MSDs complaints. Keywords: ages, years of service, working postures, musculoskeletal disorders complaints